The effects of the physical environment to learning a case study of a private elementary school in Dagupan City, Pangasinan - Nazareno, Jholly-Anna G.; Brasileno, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The purpose of this study is to find out whether the physical learning environment has an effect on student learning and whether the current interior design of a private elementary school classroom (Mother Goose Special School System, Inc.) in Dagupan City, Pangasinan, in terms of aesthetics, comfort and acoustics is effective to learning. This qualitative study made use of a descriptive methodology, using the Department of Education facilities manual and the theory of environmental determinism. A purposive sampling design was used to select the respondents for this study. The classroom?s physical environment was photo- documented and observed. A survey on the perception of comfort, aesthetics and acoustics of the classroom?s physical environment on selected 77 6th grade students and in- depth interviews with 2 faculty members was conducted. The results of the study showed that the school, particularly the selected classroom adheres to the standards of the Educational Facilities Manual of the Department of Education (DepEd). Based on the DepEd standards, the classroom, in terms of aesthetics, comfort and acoustics is considered as conducive to learning. The teachers and the students agree that the physical environment of the classroom can affect learning. Users of the space find the aesthetics and comfort of the classroom effective to learning. On the contrary, despite the positive statements on the acoustics of the classroom, it was discovered that the students and faculty members had already adapted to the noise pollution inside and outside the classroom which may be due to the open classroom system originally practiced by the school. Responses on the acoustics of the classroom varied between those who are used to the open classroom layout and those who are new to it.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Classrooms -- Decoration -- Philippines -- Dagupan City